Prospective associations of health literacy with clinical outcomes in adults with CKD: findings from the CRIC study. Issue 4 (23rd June 2022) - Estrella, Mayra L; Allen-Meares, Paula; Ricardo, Ana C; Fischer, Michael J; Gordon, Elisa J; Carmona-Powell, Eunice; Sondheimer, James; Chen, Jing; Horwitz, Edward; Wang, Xue; Hsu, Jesse Y; Lash, James P; et al.
ABSTRACT: Background: Limited health literacy is associated with significant morbidity and mortality in the general population but the relation of health literacy with long-term clinical outcomes among adults with chronic kidney disease (CKD) is less clear. Methods: Prospective data from the Chronic Renal Insufficiency Cohort (CRIC) Study ( n  = 3715) were used. Health literacy was assessed with the Short Test of Functional Health Literacy in Adults (dichotomized as limited/adequate). Cox proportional hazards models were used to separately examine the relations of health literacy with CKD progression, cardiovascular event (any of the following: myocardial infarction, congestive heart failure, stroke or peripheral artery disease), and all-cause, cardiovascular and non-cardiovascular mortality. Poisson regression was used to assess the health literacy–hospitalization association. Models were sequentially adjusted: Model 1 adjusted for potential confounders (sociodemographic factors), while Model 2 additionally adjusted for potential mediators (clinical and lifestyle factors) of the associations of interest. Results: In confounder-adjusted models, participants with limited (vs adequate) health literacy [555 (15%)] had an increased risk of CKD progression [hazard ratio (HR) 1.34; 95% confidence interval (CI) 1.06–1.71], cardiovascular event (HR 1.67; 95% CI 1.39–2.00), hospitalization (rate ratio 1.33; 95% CI 1.26–1.40), and all-cause (HR 1.54; 95% CI 1.27–1.86), cardiovascular (HR 2.39; 95% CI 1.69–3.38) and non-cardiovascular (HR 1.27; 95% CI 1.01–1.60) mortality. Additional adjustments for potential mediators (Model 2) showed similar results except that the relations of health literacy with CKD progression and non-cardiovascular mortality were no longer statistically significant. Conclusions: In the CRIC Study, adults with limited (vs adequate) health literacy had a higher risk for CKD progression, cardiovascular event, hospitalization and mortality—regardless of adjustment for potential confounders.